Modal Sosial: Kendala Penanganan Dokter dan Bidan untuk Meminimalkan Kelumpuhan Janin Akibat Takut pada Ibu Hamil - Pratiwi, Martin (Postgraduate, University of Mataram, 2024)
This study aims to analyze the obstacles faced by doctors and midwives in minimizing the risk of fetal paralysis due to pregnant women's fear. The fear experienced by pregnant women can influence medical decisions made by doctors and midwives, leading to complications during pregnancy and childbirth. The research involves qualitative analysis from the perspectives of practitioners in various healthcare facilities. Findings reveal various relationships between factors and levels of maternal fear. Firstly, there is no significant relationship between the age of pregnant women and their fear levels. Secondly, maternal education significantly impacts fear levels, with highly educated pregnant women exhibiting lower fear levels, while those with lower education experience higher fear levels. Thirdly, maternal employment status is significantly related to anxiety levels, indicating that working pregnant women may experience higher levels of fear than non-working counterparts. Qualitative analysis indicates that nulliparous women tend to have greater fear of labor pain and pre-delivery concerns. BMI has a significant relationship with anxiety levels, suggesting that pregnant women with higher BMI may experience higher fear levels. Lastly, spousal support plays a crucial role in anxiety levels, with pregnant women receiving greater support from their husbands tending to have lower levels of fear.